Incidence of and risk factors for thromboembolism during pregnancy and postpartum: A 10-year nationwide population-based study - Ji Eun Park; Yongwhi Park; Jin-Sung Yuk (Elsevier, 2021)
Objective: Knowledge of the incidence of pregnancy-related thromboembolism and its risk factors is clinically important because thromboembolism is the leading cause of maternal death. However, there are insufficient large population-based studies on this topic. The purpose of this study was to estimate the incidence of and identify the risk factors for thromboembolism during pregnancy and puerperium. Materials and methods: We analyzed data from 2007 to 2016 using the Health Insurance Review and Assessment Service (HIRA) database. Women who gave birth in the Republic of Korea were identified. Thromboembolism was defined as the simultaneous presence of both the diagnostic and test codes. Risk factors for thromboembolism were identified using logistic regression. Results: A total of 1,188 delivery episodes with thromboembolism were extracted from 4,243,393 delivery episodes. The incidence of thromboembolism was 0.28 per 1,000 deliveries, and it increased over the 10-year period. The incidence of antepartum thromboembolism was 0.1 per 1,000 deliveries (418 cases), and the incidence of postpartum thromboembolism was 0.18 per 1,000 deliveries (770 cases). Thromboembolism was associated with ovarian hyperstimulation syndrome, low socioeconomic status, multiple birth, cesarean birth, preeclampsia, postpartum hemorrhage, placenta previa, advanced maternal age, hyperemesis and primiparity. The factors associated with mortality from thromboembolism were cesarean birth and preterm premature rupture of membranes. Conclusion: The incidence of pregnancy-related thromboembolism increased over the 10-year study period. Low socioeconomic status, ovarian hyperstimulation syndrome, cesarean delivery and premature rupture of membranes were high-risk factors. This study provides an important reference for thromboprophylaxis for pregnancy-related thromboembolism.